A high-rate and long cycle life solid-state lithium–air battery. Issue 12 (5th November 2015) - Zhu, X. B.; Zhao, T. S.; Wei, Z. H.; Tan, P.; An, L.
Abstract : A novel silicone-oil film blocks H2 O and CO2 from reaching reaction sites but allows a high rate of O2 transfer. Abstract : Lithium–air batteries are currently limited to being operated under pure oxygen rather than ambient air, primarily due to the discharge product, lithium peroxide, reacting with water and carbon dioxide in ambient air to produce lithium carbonate, which renders the battery irreversible. A solution to this debilitating problem is to install an oxygen selective membrane that only allows oxygen to enter the battery. While theoretically sound, this method causes a significant decrease in the oxygen transfer rate due to a limited oxygen permeation area of the planar membrane and an increase in the oxygen transport distance from the membrane to the reaction sites. In this work, we create a novel solid-state lithium–air battery having a porous LATP cathode, designed using silicone-oil film coated pores that block water vapor and carbon dioxide from reaching reaction sites, but allow a high rate of oxygen transfer owing to an increase in the specific area of the films and a reduced oxygen transfer resistance. This battery can operate in ambient air at 5000 mA h gcarbon −1 for 50 cycles (125 days). Moreover, the charge/discharge rate reaches as high as 2.0 mA cm −2, a value which is about 40 times higher than that of conventional lithium–air batteries having an oxygen selective membrane external to the cathode.